Facile Synthesis and Enhanced Photocatalytic Properties of La2O3/SrSn(OH)6 Nanorods - Zhang, Yong; Zhuang, Lihong; Tao, Feihu; Xue, Zeyang; Pei, Lizhai (Current Nanoscience, 2023)
Background: The efficient removal of the environmental organic pollutants using the photocatalytic technology catalyzed by semiconductors has attracted great research interest in recent years. La2O3/SrSn(OH)6 nanorods show enhanced photocatalytic activity towards crystal violet (CV). Objective: The aim of this study is to obtain La2O3/SrSn(OH)6 nanorods by a simple hydrothermal route using lanthanum acetate and SrSn(OH)6 nanorods, and explore the photocatalytic properties for CV degradation. Methods: La2O3/SrSn(OH)6 nanorods were obtained by a hydrothermal route using lanthanum acetate and SrSn(OH)6 nanorods and characterized by X-ray diffraction (XRD), transmission electron microscopy, X-ray photoelectron spectroscopy (XPS), diffuse reflectance spectroscopy (DRS), photoluminescence (PL) and photocatalytic experiments. Results: The composite nanorods comprise hexagonal SrSn(OH)6 and cubic La2O3 phases. Some nanoscale particles attach to the surface of the nanorods with a diameter and length of about 100 nm and 1 μm, respectively. La2O3/SrSn(OH)6 nanorods show a lower band gap value than the SrSn(OH)6 nanorods. The photocatalytic reaction rate constant for the CV degradation using 15wt.%- La2O3/SrSn(OH)6 nanorods is 3 times higher than that of the pure nanorods. Conclusion: La2O3/SrSn(OH)6 nanorods possess good reusability and stability for CV removal. The photocatalytic activity for the CV removal of the SrSn(OH)6 nanorods can be greatly enhanced by La2O3.
Keywords: photocatalytic properties